2007
DOI: 10.1093/aje/kwm029
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Organophosphate Metabolite and Organochlorine Levels and Performance on the Brazelton Neonatal Behavioral Assessment Scale in a Multiethnic Pregnancy Cohort

Abstract: Prenatal exposures to organophosphate pesticides and polychlorinated biphenyls have been associated with abnormal neonatal behavior and/or primitive reflexes. In 1998-2002, the Mount Sinai Children's Environmental Health Center (New York City) investigated the effects of indoor pesticide use and exposure to polychlorinated biphenyls on pregnancy outcome and child neurodevelopment in an inner-city multiethnic cohort. The Brazelton Neonatal Behavioral Assessment Scale was administered before hospital discharge (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
247
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(261 citation statements)
references
References 25 publications
9
247
2
3
Order By: Relevance
“…The results of this study suggest that prenatal exposure to DDE is not associated with a measurable damage in neurological functions present during the first month of age and are consistent with those of previous studies (Stewart et al, 2000;Engel et al, 2007;Fenster et al, 2007) that evaluated the same association, using only the Brazelton Scale. However, it cannot be ruled out that latent neurodevelopment impairment emerges at later ages as has been found in other studies (Ribas-Fito´et al, 2003Eskenazi et al, 2006;Torres-Sa´nchez et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study suggest that prenatal exposure to DDE is not associated with a measurable damage in neurological functions present during the first month of age and are consistent with those of previous studies (Stewart et al, 2000;Engel et al, 2007;Fenster et al, 2007) that evaluated the same association, using only the Brazelton Scale. However, it cannot be ruled out that latent neurodevelopment impairment emerges at later ages as has been found in other studies (Ribas-Fito´et al, 2003Eskenazi et al, 2006;Torres-Sa´nchez et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Three of them with median ranged from 0.10 to B8 parts per billion (p.p.b.) wet basis DDE concentrations (Stewart et al, 2000;Engel et al, 2007;Fenster et al, 2007) found no association between prenatal DDE exposure and neonatal neurodevelopment. In contrast, Rogan et al (1986), with the largest sized sample and median maternal DDE exposure of 12.6 p.p.b., reported a significant association between prenatal DDE exposure and hyporeflexia, while Sagiv et al (2008) observed irritability and decreased attention at 2 weeks of age with lower (0.48 p.p.b.)…”
Section: Introductionmentioning
confidence: 93%
“…Of the WISC-IV indices used as end points, the Working Memory Index was the most strongly associated with CPF exposure in this population. Although no other epidemiologic studies have evaluated the neurotoxicity of prenatal CPF exposure on cognitive development at the time of school entry, several prior studies, using the present biomarker of exposure, have reported evidence of early cognitive and behavioral effects associated with a urinary biomarker of nonspecific OP exposure (Engel et al 2007;Eskenazi et al 2007;Young et al 2005). Outcomes associated with exposure in these studies, as well as in our own earlier work (Rauh et al 2006), have included attentional problems (e.g., Marks et al 2010).…”
Section: Discussionmentioning
confidence: 82%
“…Using urinary metabolites as the biomarker of exposure, several different birth cohort studies have reported that prenatal maternal nonspecific OP exposure was associated with abnormal neo natal reflexes (Engel et al 2007;Young et al 2005), mental deficits and pervasive development disorder at 2 years (Eskenazi et al 2007), and attention problem behaviors and a composite attention-deficit/hyperactivity disorder indicator at 5 years of age (Marks et al 2010). …”
mentioning
confidence: 99%
“…A study in New York City found a possible link between prenatal indoor pesticide exposure and abnormal neonatal reflexes, although the authors cautioned they were unable to accurately identify to which pesticides mothers were exposed (Engel et al, 2007). Researchers, identifying the critical prenatal window when children may be particularly vulnerable to neurobehavioral effects of pesticides, monitored 224 mothers' serum levels of DDE, a metabolite of DDT, during each trimester of pregnancy and discovered that levels during the first trimester were linked to reduced psychomotor development index scores-but not mental development index scores -during the first year of life (Torres-Sanchez et al, 2007).…”
Section: Links Between Neurobeha Vior and Pesticidesmentioning
confidence: 99%